Kunst ohne Unikat : Edition Artelier 1985-1998. - Neuen Galerie am Landesmuseum Joanneum, Graz; Künstlerhaus, Graz; Barak, Ami; Breicha, Otto; Caramelle, Ernst; Crüwell, Konstanze; Draxler, Helmut; Durschei, Victor; Feng, Mengbo; Fiedler, Elisabeth; Fleck, Robert; Fuchs, Rainer; et al. (Graz : Neue Galerie am Landesmuseum Joanneum, 1998)
Andraschek, Iris ; Anüll, Ian ; Armleder, John M. ; Attersee, Christian Ludwig ; Baldessari, John ; Baz, Mohamed El ; Blum, Heiner ; Bonin, Cosima von ; Bonk, Ecke ; Bretterbauer, Gilbert ; Bühlmann, Max ; Burki, Marie José ; Caramelle, Ernst ; Creimer, Georgia ; Czernin, Franz Josef ; Danner, Josef ; David, Jiri ; Deutsch, Johannes ; Dubner, Bronislava A. ; Feng Mengbo ; Förg, Gunther ; G.R.A.M. ; Gasteiger, Jakob ; Geers, Kendell ; Geiger, Marcus ; Grünfeld, Thomas ; Heinzmann, Thilo ; Hoeck, Richard ; Ikemura, Leiko ; Jones, Ronald ; Kappl, Franco ; Kienzer, Michael ; Kippenberger, Martin ; Koch, Udo ; Kogler, Peter ; Kosuth, Joseph ; Kowanz, Brigitte ; Kunzmann, Andreas ; Kupelwieser, Hans ; Lawler, Louise ; LeWitt, Sol ; Locher, Thomas ; Mayer, Hans-Jörg ; Mohiden, Hoshyar ; Müller, Christian Philipp ; Myslowski, Tadeusz ; Nannucci, Maurizio ; Nessmann, Stefan ; Nogueira, Lucia ; Oehlen, Albert ; Ramati, Roman Haubenstock ; Rehberger, Tobias ; Reiterer, Werner ; Rinn, Rivka ; Rockenschaub, Gerwald ; Samba, Cheri ; Schlegel, Eva ; Schlick, Jörg ; Schmalix, Hubert ; Schmatz, Ferdinand ; Schuster, Michael ; Skerbisch, Hartmut ; Skreiner, Gunther ; Stadler, Werner ; Steinbach, Haim ; Steinbrener, Christoph ; Stimm, Thomas ; Stock, Christian ; Stückler, Wolfgang ; Troger, Gustav ; Tusek, Mitja ; Urban, Hartmut ; Wagnest, Matta ; Walde, Martin ; Wanner, Franz ; Weibel, Peter ; Weigand, Hans ; West, Franz ; Wilson, Fred ; Wizemann, Günther ; Woertl, Hansi ; Wurm, Erwin ; X, Robert Adrian ; Zehrer, Joseph ; Zinganel, Michael ; Zobernig, Heimo
biografie
Kunst ohne Unikat : Edition Artelier 1985 - 1998, Neuen Galerie am Landesmuseum Joanneum, im Künstlerhaus, Graz, 26. September bis 26. Oktober 1998
Duits
Engels
Frans
boek